Induction of NTPDase1/CD39 by Reactive Microglia and Macrophages Is Associated With the Functional State During EAE - Jakovljevic, Marija; Lavrnja, Irena; Bozic, Iva; Milosevic, Ana; Bjelobaba, Ivana; Savic, Danijela; Sévigny, Jean; Pekovic, Sanja; Nedeljkovic, Nadezda; Laketa, Danijela (Frontiers in Neuroscience, 2019)
Purinergic signaling is critically involved in neuroinflammation associated with multiple sclerosis (MS) and its major inflammatory animal model, experimental autoimmune encephalomyelitis (EAE). Herein, we explored the expression of ectonucleoside triphosphate diphosphohydrolase1 (NTPDase1/CD39) in the spinal cord, at the onset (Eo), peak (Ep) and end (Ee) of EAE. Several-fold increase in mRNA and in NTPDase1 protein levels were observed at Eo and Ep. In situ hybridization combined with fluorescent immunohistochemistry showed that reactive microglia and infiltrated mononuclear cells mostly accounted for the observed increase. Colocalization analysis revealed that up to 80% of Iba1 immunoreactivity and ~ 50% of CD68 immunoreactivity was colocalized with NTPDase1, while flow cytometric analysis revealed that ~ 70% of mononuclear infiltrates were NTPDase1+ at Ep. Given the main role of NTPDase1 to degrade proinflammatory ATP, we hypothesized that the observed up-regulation of NTPDase1 may be associated with the transition between proinflammatory M1-like to neuroprotective M2-like phenotype of microglia/macrophages during EAE. Functional phenotype of reactive microglia/macrophages that overexpress NTPDase1 was assessed by multi-image colocalization analysis using iNOS and Arg1 as selective markers for M1 and M2 reactive states, respectively. At the peak of EAE NTPDase1 immunoreactivity showed much higher co-occurrence with Arg1 immunoreactivity in microglia and macrophages, compared to iNOS, implying its stronger association with M2-like reactive phenotype. Additionally, in ~80% of CD68 positive cells NTPDase1 was coexpressed with Arg1 compared to negligible fraction coexpresing iNOS and ~15% coexpresing both markers, additionally indicating prevalent association of NTPDase1 with M2-like microglial/macrophages phenotype at Ep. Together, our data suggest an association between NTPDase1 up-regulation by reactive microglia and infiltrated macrophages and their transition towards antiinflammatory phenotype in EAE.